1999
DOI: 10.1055/s-2008-1072289
|View full text |Cite
|
Sign up to set email alerts
|

Rehbein's Procedure for Hirschsprung's Disease. An Appraisal of 45 Years*

Abstract: A retrospective follow-up study of all children treated for Hirschsprung's disease over the last 45 years at the Department of Pediatric Surgery, Children's Hospital, Bremen was done to evaluate the results of Rehbein's procedure. A total of 416 children underwent Rehbein's lower anterior resection. The postoperative outcome was analysed in detail for early and late complications like wound infection, pelvic abscess, anastomotic stenosis, anastomotic insufficiency, postoperative enterocolitis, persistence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The Rehbein-procedure (RB) for children with Hirschsprung Disease (HD) is one of the techniques mostly used in Europe for the past 25 years [1, 2]. In our clinic good long-term results were seen despite the fact that a relatively large aganglionotic segment was left in situ compared with other techniques as the Soave, Swenson, or Duhamel procedures [3].…”
Section: Introductionmentioning
confidence: 85%
“…The Rehbein-procedure (RB) for children with Hirschsprung Disease (HD) is one of the techniques mostly used in Europe for the past 25 years [1, 2]. In our clinic good long-term results were seen despite the fact that a relatively large aganglionotic segment was left in situ compared with other techniques as the Soave, Swenson, or Duhamel procedures [3].…”
Section: Introductionmentioning
confidence: 85%
“…Soiling at least once a week occurred in 11 (27 %) of our 41 patients, 6 of whom had undergone a sphincteromyectomy. Approximately 85 % of the patients reported by Fuchs et al [3] had excellent or good function at follow up. This could be compared with 66 % of our cases having good function at follow up.…”
Section: Discussionmentioning
confidence: 88%
“…One exception is the study by Thepcharoennirund reporting very good results in 55 of 73 patients operated with Rehbein's procedure [15]. Fuchs et al [3] also recently reviewed a large series of 146 patients operated with Rehbein's method that were followed for an average period of 4 years. They included a historical series and found that constipation was reported in 15.4 % of the patients and faecal incontinence in 5.4 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the lower urinary tract dysfunctions encountered after HD operations, urinary retention and enuresis have been the most emphasized findings during the early postoperative period [14][15][16][17][18]. Enuresis has been defined with an incidence of 5.4%, 10.4%, 15.3%, and 14.3% after Rehbein, Swenson, Soave, and Duhamel operations, respectively [10].…”
Section: Discussionmentioning
confidence: 99%